PRODUCTIVITY AND DEVELOPMENT STRATEGY OF SEAWEED ((Kappaphycus alvarezii) ) IN BANTEN BAY WHICH IS VULNERABLE TO ENVIRONMENTAL CHANGE - Farkan, Mochammad; Dewi, Priyantini; Samsu Harapan, Sri Budiani; Suharyadi, Suharyadi; Novriadi, Romi; Awaludin, Asep (Jakarta Technical University of Fisheries, 2023)
Seaweeds is a fishery commodity that has economic value and generates quite a large amount of foreign exchange. However, in its development, production fluctuated and not all marine locations could maintain seaweed throughout the year. Relatively low production costs and a market that is available at any time. The purpose of this study was to analyze the productivity and development strategies for Euchema cotonii grass cultivation in Banten Bay. Changes in spatial planning, land conversion, industrial activities in the western and eastern parts, waste disposal through the river in this section and the excavation of sand mines have made the bay very vulnerable to the environment. The location of this activity is the coast and waters around the island of Banten Bay. The method of data collection is the measurement of water quality parameters in the field, surveys, interviews, discussions and limited participation in seaweed cultivation locations. The data analysis method is descriptive and uses the SWOT tool (Strength, Weakness, Opportunities and Threats) and uses SPSS version 25, excel and to assess sustainability using raphfish. Research results show. Water quality conditions are in accordance with the growth of seaweed. Production starting in 1987 fluctuated and conditions were stagnant in the last 3 years. The recommended strategy for increasing production is increasing grass productivity through expanding areas that have mapped potential and land suitability with applied technology, competent human resources, using superior seeds and reducing environmental pollution by industry and sand mining. KEYWORDS: Seaweed; Banten Bay; Environmental pollution; Serang.